'University is a non‐Muslim experience, you know? The experience is as good as it can be': Satisfied settling in Muslim students' experiences and implications for Muslim student voice. (6th June 2021) - Islam, Maisha; Mercer‐Mapstone, Lucy
Abstract : We report findings from a cross‐institutional investigation testing the applicability of a new concept, 'satisfied settling', which describes the ways in which students are unconsciously 'settling for less' in terms of their university experiences. The context of exploration for this article was that of Muslim students' experiences as a critical area which has received little previous focus. Our results describe a staged cognitive process undertaken by students to subconsciously excuse institutional failures to support their religious needs by settling for lower levels of satisfaction. The 'counter stories' told by 19 Muslim students (via semi‐structured interviews) detail how their voices are heard or silenced around the deep importance of religious provisions in their university experiences. Satisfied settling was ultimately found to translate across institutional contexts, and the applicability of the concept is discussed in extending to other marginalised student groups.